The hidden side of calf claudication: Hemodynamic and clinical results of treadmill testing in 584 patients complaining of isolated exertional calf pain. (December 2020) - Ramondou, Pierre; Sempore, Wendsendaté Yves; Guilleron, Céline; Hersant, Jeanne; Ouedraogo, Nafi; Abraham, Pierre; Henni, Samir
Abstract: Background and aims: Calf pain is the most frequent symptom of arterial claudication. We hypothesized that patients with self-reported isolated calf claudication have frequent exertional non-calf symptoms during objective laboratory testing, and that many would show not only distal, but also proximal ischemia. Methods: We retrospectively analyzed the patients referred since 2016 for exercise transcutaneous oxygen pressure (Ex-tc p O2 ). The Edinburgh Claudication Questionnaire (ECQ) was self-completed before and during a treadmill test. For calf and non-calf (buttock and thigh) Ex-tc p O2, a lowest decrease of rest of oxygen pressure (DROP) < −15 mmHg was indicative of ischemia. We selected the patients that reported calf claudication only and analyzed minimal DROP and per-test ECQ observations. Results: Exertional symptoms on a treadmill occurred in 526 (90.1%) of the 584 patients analyzed (65.6 ± 11.4 years old), with 391 (74.3%) of these symptoms affecting only the calf. Isolated calf ischemia with or without symptoms was found in only 139 (23.8%) patients. Overall, among the 584 patients self-reporting isolated calf symptoms, a perfect concordance between symptoms on a treadmill and Ex-tc p O2 (i.e. calf symptoms associated to calf ischemia) was observed in only 114 (19.5%) cases. Conclusions: Our study demonstrated that patients self-reporting exertional limb pain strictly limited to the calf may also have non-calf claudication on a treadmill and frequently show not-only-calf ischemia. These observations are important when planning reeducation or when studying the tissue consequences of ischemia in patients with claudication. Graphical abstract: Image 1 Highlights: Calves are considered optimal sites for analyzing muscle ischemia in claudication. We measured ischemia and symptoms on a treadmill in 584 claudicants with calf pain. Only 77% of patients with an ABI <0.90 had calf pain and ischemia on the treadmill. 35% of patients with an ABI not <0.90 had calf pain and ischemia on the treadmill. Many discrepancies exist between pain by history and on a treadmill and ischemia.